Politeness Principles on Talk Show Najwa's Notes "Exclusive: Ma'ruf Amin about Forgotten Vice President" - Annisa Agustiyani Ica; Asep Firdaus; Fauziah Suparman (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The aim of this study are to describe the implicature of illocutionary speech acts on the Najwa Shihab Talk Show, analyze the compliance with politeness principles on the Najwa Shihab talk show, and analyze the violation of politeness principles on the Najwa Shihab talk show. This study uses a qualitative approach with a descriptive method. The data source was obtained from Najwa Shihab's Youtube video on the talk show Najwa's notes "Exclusive: Ma'ruf Amin about the Forgotten Vice President" and Mata Najwa's Talk Show "Don't Wait Your Turn" in the form of conversation transcripts. Collecting data using the method of listening and note-taking techniques. The results of this study are as follows, first the implicature of illocutionary speech acts, including assertive, directive, expressive, and commissive. Second, obeying the principle of politeness. Thirdly violating the principle of politeness. The politeness principle includes the maxim of wisdom, the maxim of generosity, the maxim of praise, the maxim of humility, and the maxim of sympathy. Keywords: illocutionary speech acts, speech, compliance with politeness principles Abstrak Tujuan penelitian ini untuk mendeskripsikan implikatur tindak tutur ilokusi pada Talk Show Najwa Shihab, analisis pematuhan prinsip kesantunan pada Talk Show Najwa Shihab, dan analisis pelanggaran prinsip kesantunan pada Talk Show Najwa Shihab. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Sumber data diperoleh dari video Youtube Najwa Shihab acara talk show Catatan Najwa “Eksklusif: Ma’ruf Amin soal Wapres yang Terlupakan” dan Talk Show Mata Najwa “Jangan Tunggu Giliran” berupa transkripsi percakapan. Pengumpulan data menggunakan metode simak dan teknik simak catat. Hasil penelitian ini adalah sebagai berikut, pertama implikatur tindak tutur ilokusi, meliputi asertif, direktif, ekspresif, dan komisif. Kedua, pematuhan prinsip kesantunan. Ketiga, pelanggaran prinsip kesantunan. Prinsip kesantunan meliputi maksim kearifan, maksim kedermawanan, maksim pujian, maksim kerendahan hati, dan maksim kesimpatian. Kata kunci: tindak tutur ilokusi, tuturan, pematuhan prinsip kesantunan